RESEARCH ON SIZE EFFECT ON FRACTURE TOUGHNESS OF PIPELINE STEEL - ZHEN Ying; YI HaiJiao; CAO YuGuang; ZHANG ShiHua; SHI YongJin (Jixie qiangdu)
As a parameter characterizes the ability to resist crack propagation,fracture toughness plays an important role in evaluation of pipeline integrity. It is of both scientific and engineering significance to carry out a thorough study on its size effect.At present,the research on size effect of fracture toughness of metal materials is mainly focused on the linear elastic fracture parameter stress intensity factor K,and mostly only the influence of specimen thickness is considered. In order to establish a systematic law of size effect on high strength and high toughness pipe steel,a three-dimensional finite element model of standard single-edge notched beam（ SENB） specimens based on GTN model was set up. The ductile fracture process of this specimens under displacement load was simulated. The Crack-tip Opening Displacement（ CTOD） and Crack-tip Opening Angle（ CTOA）were selected to characterize the fracture behavior. The distribution law of them along the specimen thickness direction was analyzed,and the effects of crack depth and specimen thickness were also studied. At the same time,the stress triaxiality was selected to evaluate the constraint level,so as to explain the cause of the size effect. The results show that the fracture toughness along the thickness direction remains unchanged within a certain range and reaches peak value at the free surface. The crack depth has little effect on fracture toughness and it decrease with the increase of specimen thickness.